2005
DOI: 10.1007/s11270-005-3427-3
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Chromium Electrodialytic Migration in CCA-Treated Timber Waste

Abstract: Chromated copper arsenate (CCA)-treated timber waste is hazardous for the environment due to the leakage of copper, chromium as well as arsenic to the soil and the groundwater. The study concentrates on electrodialytic removal of copper and chromium and their migration behavior in the wood chips and sawdust matrix in an applied electric field. The method is based on the movement of the charged particles in the electric field, enhanced by incubation with oxalic acid (2.5% w/w) and various placement of the conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Thus, low pH conditions (<5) would be the most favourable for efficient electromigration of the small divalent Cu cations towards the cathode, and at least the maximum pH should be maintained at <10 to avoid precipitation of Cu hydroxides, co-precipitation of As and reversal in ionic charge. When the wood chips contained extraction residuals of oxalic acid, electrokinetic treatment turned the catholyte solution brown in colour and some dark, hard precipitate was deposited on the cathode surface, like reported previously [32]. Cu 2+ was obviously reduced to elemental Cu.…”
Section: Removal Of Coppersupporting
confidence: 72%
See 2 more Smart Citations
“…Thus, low pH conditions (<5) would be the most favourable for efficient electromigration of the small divalent Cu cations towards the cathode, and at least the maximum pH should be maintained at <10 to avoid precipitation of Cu hydroxides, co-precipitation of As and reversal in ionic charge. When the wood chips contained extraction residuals of oxalic acid, electrokinetic treatment turned the catholyte solution brown in colour and some dark, hard precipitate was deposited on the cathode surface, like reported previously [32]. Cu 2+ was obviously reduced to elemental Cu.…”
Section: Removal Of Coppersupporting
confidence: 72%
“…A quantitative mass balance was not determined, however, these amounts were significant as compared to the total amount of Cr removed from wood chips, 700-800 mg. In some previous papers movement of Cr towards the anode has been attributed to the formation of anions from Cr(VI) [26,30,32]. Radivojevic and Cooper [44] have found that in the presence of wood, Cr(III) is easily oxidized to Cr(VI) at pH ≥ 8.5.…”
Section: Removal Of Chromiummentioning
confidence: 99%
See 1 more Smart Citation
“…One of these emerging technologies are electrokinetic remediation techniques, which offer a great potential for the removal of charged contaminants from sludge [4,5], soil [6], sediments [2] and copper chromated arsenate (CCA)-treated timber waste [7,8]. The electrokinetic phenomenon employs a low-level direct current across the contaminated medium, which induces the mobility of charged contaminants due to electromigration and electroosmotic flow [9].…”
Section: Introductionmentioning
confidence: 99%
“…Treating methods for these materials that have been evaluated include incineration (combustion) (Hirata et al 1993;Nurmi 1996), thermal disposal (pyrolysis) (Hata et al 2003;Helsen et al 2003), liquefaction (Lin and Hse 2005), steam treatment (Smith and Shiau 1996;Shiau et al 2000;, formation into wood composites (Wu et al 2010) and electrodialytic remediation (Virkutyte et al 2005). Chemical extraction can be a viable alternative process to remove and reuse metals from wood and produce decontaminated wood.…”
Section: Introductionmentioning
confidence: 99%